2020
DOI: 10.1172/jci131838
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning reveals serum sphingolipids as cholesterol-independent biomarkers of coronary artery disease

Abstract: BACKGROUND.Ceramides are sphingolipids that play causative roles in diabetes and heart disease, with their serum levels measured clinically as biomarkers of cardiovascular disease (CVD). METHODS.We performed targeted lipidomics on serum samples from individuals with familial coronary artery disease (CAD) (n = 462) and population-based controls (n = 212) to explore the relationship between serum sphingolipids and CAD, using unbiased machine learning to identify sphingolipid species positively associated with CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
146
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 71 publications
(88 reference statements)
5
146
1
1
Order By: Relevance
“…Dots and lines in red represent significant association biomarkers for various conditions including cancer, neurodegenerative, metabolic, autoimmune. and vascular diseases [25,[44][45][46][47][48][49][50]. In the current study, we observed alterations of plasma sphingosine-1-phosphate (S1P) species in a cohort of aged cognitively normal subjects as well as people with vascular cognitive impairment (VCI) and Alzheimer's disease (AD).…”
Section: Discussionmentioning
confidence: 84%
“…Dots and lines in red represent significant association biomarkers for various conditions including cancer, neurodegenerative, metabolic, autoimmune. and vascular diseases [25,[44][45][46][47][48][49][50]. In the current study, we observed alterations of plasma sphingosine-1-phosphate (S1P) species in a cohort of aged cognitively normal subjects as well as people with vascular cognitive impairment (VCI) and Alzheimer's disease (AD).…”
Section: Discussionmentioning
confidence: 84%
“…A new approach to identify associations between serum ceramides and coronary artery disease (CAD) was introduced by Poss et al ( 50 ). They performed targeted lipidomics on serum samples from individuals with familial CAD ( n = 462) and population-based controls ( n = 212) to study the association between serum sphingolipids and CAD, using unbiased machine learning to find sphingolipids related with CAD.…”
Section: Ceramide Score As the Clinical Solutionmentioning
confidence: 99%
“…In addition to the intrinsic biological complexity, lack of big cohorts due to limitations in sample gathering or high analytical costs, and intragroup variability of measurements further complicate these studies. In this context, recent works have shown that implementation of artificial intelligence approaches can help to unravel disease-specific markers and pathological mechanisms even in data-limited regimes [48][49][50][51][52]. Therefore, using a novel approach, we have combined metabolomic and proteomic measurements with machine intelligence modeling and synthetic data generation [51,53,54] to identify molecular patterns that can discriminate malignant from benign biliary strictures.…”
Section: Introductionmentioning
confidence: 99%